(untitled) (XXI Century. Spanish Literature and Culture, 2019)
This paper describes how Ínsula magazine received the transformation of Spanish narrative between 1966 and 1985. More specifically, the work focuses on the young authors of “the 1968 generation”, who began to publish since the late 60s. By then there was a confrontation between traditional realism and experimental renovation. However, the young writers were not interested in this dialectic. They prefer to practice different narrative models, they have an eclectic conception of the fictional genre and the magazine values ​​them positively.